Book Review: W. Bołoz, Kościół i ekologia. W obronie człowieka i środowiska naturalnego, Wyd. Homo Dei, Kraków 2010 - Smoderek, Karolina (Problemy Ekorozwoju, 2011)
Reading the book Church and ecology allows you to understand the axiological foundations of environmental protection rooted in Christianity. Written in a balanced way, it presents the basics of ecological reasoning, taking into account a wide range of issues. A publication not only for ecologists and students of environmental protection.